Climate-Smart Solutions for MENA’s Food System - from Fragility to Resilience - Abousabaa, Aly (International Center for Agricultural Research in the Dry Areas, 2023)
The presentation is linked to the role of agrobiodiversity in Tajikistan for the world food security roundtable discussion at COP27